Fatty Acids 2017
DOI: 10.5772/intechopen.68544
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids’ Profiles of Aquatic Organisms: Revealing the Impacts of Environmental and Anthropogenic Stressors

Abstract: There is a great concern about the impacts of climate changes namely due to salinity seawater and temperature alterations in aquatic organisms with the estuarine and coastal environments being the major affected areas. The intensive usage of chemicals in an indiscriminate way in agriculture practices, achieving, in some cases, values above the limits of contamination authorized by the European legislation, also drastically affects the surrounded estuarine areas with profound consequences to the water quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Seaweeds are known as a low-energy, low-caloric food, and an explanation for this is the low content in lipids. Besides that, in recent years, interest in the lipid composition of marine algae has raised considerably because a big part of seaweed lipid content is constituted by ω-3 and ω-6 PUFAs, specifically α-linolenic (18:3ω-3), octadecatetraenoic (18:4ω-3), arachidonic (20:4ω-6), and eicosapentaenoic (20:5ω-3) acids [27][28][29]. Indeed, algae are essentially the only organisms able to produce long-chain PUFAs, ranging from 14 to 24 carbons, due to the presence of specific enzymes responsible for desaturation processes [29,30].…”
Section: Pufasmentioning
confidence: 99%
See 1 more Smart Citation
“…Seaweeds are known as a low-energy, low-caloric food, and an explanation for this is the low content in lipids. Besides that, in recent years, interest in the lipid composition of marine algae has raised considerably because a big part of seaweed lipid content is constituted by ω-3 and ω-6 PUFAs, specifically α-linolenic (18:3ω-3), octadecatetraenoic (18:4ω-3), arachidonic (20:4ω-6), and eicosapentaenoic (20:5ω-3) acids [27][28][29]. Indeed, algae are essentially the only organisms able to produce long-chain PUFAs, ranging from 14 to 24 carbons, due to the presence of specific enzymes responsible for desaturation processes [29,30].…”
Section: Pufasmentioning
confidence: 99%
“…PUFAs are all the fatty acids that contain more than one unsaturation (double bond) in their backbone and include the EFAs. EFAs, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), play an important role in immunomodulation, in brain development, and in other physiological functions, such as cellular signaling, the regulation of transcription factors, and in the treatment and prevention of some cancer, ocular, cardiovascular, neurodegenerative, and autoimmune diseases [27].…”
Section: Pufasmentioning
confidence: 99%
“…Because of their importance in the health/stability of the marine ecosystem, FAs are judged to be an accurate tool in trophic interaction and stage of larval development and growth (Arts et al, 2001; Finotello et al, 2017). Recent studies have suggested that changes in FA constituents or profiles are a good tool to evaluate the effect of environmental change and exposure to contaminants in marine organisms (Gonçalves et al, 2017; Trabelsi et al, 2019). Highly unsaturated FAs, such as the eicosapentaenoic acid (C20:5n-3, EPA), docosahexaenoic acid (C22:6n-3, DHA), and arachidonic acid (C20:4n-6, ARA), are a subset of the polyunsaturated FAs (PUFAs) with a chain of 20 carbon atoms or more and with three or more double bonds that play a key role in cellular and tissue growth, energy storage and neural development (Arts et al, 2001), as well as enhancing the organisms’ adaptation to environmental stress (Neves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that bivalve nutritional quality was compromised (Jaschinski et al, 2008;Ruano et al, 2012). The higher proportion of bacterial FAs in M. liliana tissue suggests M. liliana ingested more bacteria or organic matter that had been processed via the microbial loop (Mayzaud et al, 1990;Gonçalves et al, 2017). The higher proportion of diatoms in the sediment and the shift in bivalve quality suggests the changes to the MPB community stimulated bacterial communities, which in turn lowered the quality of the bivalves.…”
Section: Figure 4 | (A)mentioning
confidence: 99%